Capecitabine and temozolomide in grade 1/2 neuroendocrine tumors: a Spanish multicenter experience. (March 2017) - Crespo, Guillermo; Jiménez-Fonseca, Paula; Custodio, Ana; López, Carlos; Carmona-Bayonas, Alberto; Alonso, Vicente; Navarro, Miguel; Aller, Javier; Sevilla, Isabel; Grande, Enrique; Gajate, Pablo; Alonso-Gordoa, Teresa; et al.
Background & methods: Capecitabine and temozolomide chemotherapy was used in 65 patients with grade 1/2 neuroendocrine tumors (NETs). 46 patients (70.8%) had pancreatic NETs (pNETs).Results: Response rate was 47.7%, with two complete responses (3.1%), 29 partial responses (44.6%) and 27 patients (41.5%) achieved stable disease. Median progression-free survival was 16.1 months (95% CI: 10.7–21.6) and overall survival was 38.3 months (95% CI: 24.6–51.9). Differences in progression-free survival and overall survival between pNETs and non-pNETs were not found. Nine (13.8%) patients experienced grade 3/4 toxicities, mainly thrombocytopenia (10.8%) and neutropenia (7.7%).Conclusion: This is the largest reported series of NETs treated with capecitabine and temozolomide in daily practice and shows that this combination is a promising treatment option for both grade 1/2 pNETs and non-pNETs.